(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
To achieve this goal, a random sample of 25 male and female students was selected from the fourth stage students applied for the academic year 2022-2023.A research tool was also prepared represented by a note card that included the three main skills, which are the planning skill and includes eight sub-skills, the implementation skill and includes nine sub-skills and the evaluation skill and includes six sub-skills. After applying the tool and analyzing the data, the results showed that the applied students possessed the skill of planning and implementation to a medium degree, while the implementation skill was weak and in light of the results, a set of conclusions, recommendations and suggestions were presented.